A Comprehensive Analysis of The Factors Influencing Electric Vehicle Purchase Intentions in Indonesia: A Study Based on The UTAUT 2 Model - Muhammad Ikhsan Hidayatullah; Ujang Sumarwan; Suhendi Suhendi (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Air pollution and climate change are critical global challenges that drive the transition toward sustainable transportation solutions, including electric vehicles (EVs). In Indonesia, EV adoption remains relatively low, making it essential to investigate the key factors influencing consumer intentions. This study focuses on the millennial generation, as they represent a significant share of the productive population, are generally more open to technological innovation, and are expected to become the primary consumers in the future EV market.Purpose: This study aims to analyze the factors influencing EV adoption in Indonesia by applying a modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model, with millennials as the key demographic segment.Design/methodology/approach: An online survey was conducted with 230 respondents, and the data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) through SmartPLS 3.0 software. The study examined nine variables: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, perceived behavioral control, and attitude toward behavior.Findings/Results: The results indicate that habit and hedonic motivation significantly influence consumers’ behavioral intention to adopt EVs. Conversely, performance expectancy and social influence were not found to mediate the relationship between exogenous variables and use behavior.Conclusion: The findings suggest that manufacturers should prioritize creating personalized consumer experiences and enhancing the social status associated with EV ownership. Furthermore, policymakers should strengthen incentives and accelerate infrastructure development to support EV adoption in Indonesia. Marketing strategies also need to integrate consumer habits and emotional drivers to speed up the adoption process.Originality/value (State of the art): This study contributes to the growing body of knowledge on EV adoption in developing countries by applying a modified UTAUT2 model with a focus on millennials. The results provide valuable insights for policymakers and industry stakeholders in designing targeted interventions to promote EV adoption. Keywords: electric vehicles, UTAUT 2, behavioral intention, sustainable transportation, structural equation modeling (SEM)